Kesan Penambahan Tiubnano Karbon terhadap Pertumbuhan Lapisan Sebatian antara Logam Sistem Pateri Sn-Ag-Cu/Cu akibat Penuaan Terma (Effect of carbon nanotube addition on the growth of intermetallic layer of Sn-Ag-Cu solder system under thermal aging) - Ismail, Norliza; Jalar, Azman; Abu Bakar, Maria; Ismail, Roslina (Penerbit Universiti Kebangsaan Malaysia, 2018)
Effect of carbon nanotube (CNT) on the growth of intermetallic compound (IMC) layer of 96.5Sn-3.0Ag-0.5Cu/Cu substrate lead free solder system has been investigated. Sn-Ag-Cu alloy powder (SAC305) was mixed with 0.02 weight percent of CNT to produce SAC-CNT solder paste. Both SAC305 and SAC305-CNT solder paste has been manually printed on the printed circuit board (PCB) with the copper (Cu) surface finish by using stencil printing method. Printed samples were reflowed at temperature 260°C. Soldered samples underwent thermal aging test for the period of 200, 400, 600, 800 and 1000 h using high temperature storage (HTS) oven at a constant temperature 150°C. The thickness of IMC layer was measured by Infinite Focus Measurement (IFM®) equipment. The results found that growth rates of IMC layer for SAC305/Cu-CNT system is 25% lower than SAC/Cu system. Therefore, addition of CNT proposed can retard about 25% of IMC layer growth under thermal aging.